Anti-carbamylated proteins antibody repertoire in rheumatoid arthritis: evidence of a new autoantibody linked to interstitial lung disease. Issue 5 (10th March 2020) - Castellanos-Moreira, Raul; Rodríguez-García, Sebastian Cruz; Gomara, Maria Jose; Ruiz-Esquide, Virginia; Cuervo, Andrea; Casafont-Solé, Ivette; Ramírez, Julio; Holgado, Susana; Gómez-Puerta, Jose A; Cañete, Juan D; Haro, Isabel; Sanmarti, Raimon
Abstract : Objective: To analyse the association between anti-carbamylated protein antibodies (Anti-CarP) and interstitial lung disease (ILD) in rheumatoid arthritis (RA) patients. Methods: Cross-sectional study including RA patients fulfilling the 2010 ACR/EULAR criteria. The main population comprised two groups: (1) RA patients diagnosed with RA-ILD (RA-ILD group); (2) RA patients without ILD (non-ILD RA group). Non-ILD RA patients in whom ILD was suspected underwent a diagnostic work-up and, if ILD was diagnosed, were switched to the RA-ILD group. ILD was diagnosed by high-resolution computed tomography and confirmed by a multidisciplinary committee. An independent replication sample was also obtained. Three Anti-CarP IgG autoantibodies against fetal calf serum (Anti-FCS), fibrinogen (Anti-Fib) and chimeric fibrine/filagrine homocitrullinated peptide (Anti-CFFHP) and one Anti-CarP IgA against FCS (Anti-FCS-IgA) were determined by home-made ELISA. Associations between Anti-CarP and ILD were analysed using multivariable logistic regression adjusted by smoking, sex, age, RA disease duration, rheumatoid factor and anticitrullinated protein antibodies. Results: We enrolled 179 patients: 37 (21%) were finally diagnosed with RA-ILD. Anti-CarP specificities were more frequent in RA-ILD patients (Anti-FCS 70% vs 43%; Anti-Fib 73% vs 51%; Anti-CFFHP 38% vs 19%; Anti-CarP-IgA 51% vs 20%, p<0.05 for all comparisons). Serum titers of Anti-CarP were significantly higher in RA-ILD patients. Anti-CarP specificities showed a robust effect towards increasing the odds of ILD in the multivariate analysis (Anti-FCS (OR: 3.42; 95% CI: 1.13 to 10.40), Anti-Fib (OR: 2.85; 95% CI: 0.83 to 9.70), Anti-CFFHP (OR: 3.11; 95% CI: 1.06 to 9.14) and Anti-FCS-IgA (OR: 4.30; 95% CI: 1.41 to 13.04)). Similar findings were observed in the replication sample. Conclusions: Anti-CarP were strongly associated with ILD. The role of homocitrullination in RA-ILD merits further investigation.